1980
DOI: 10.1002/pssb.2221000107
|View full text |Cite
|
Sign up to set email alerts
|

On the Structural Transition from NaCl to CsCl Type in Alkali Hydrides

Abstract: The solid sphere ion model is used to compare specific volumes of NaCl and CsCl phases of alkali hydrides. The transition of the KoCl to CsCl type is shown to be thermodynamically possible in K, Rb, and Cs hydrides. A phase transition is detected in K H a t pressures about 40 kbar, and the T-P diagram of K H is studied. On the basis of the analysis performed, the NaCl to CsCl transition in LiH is unlikely, unless the electron configurations of the ions are changed. B npH6JIHWeHHH WeCTKHX C@ep IIpOBeHeHO CpaBHe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
(3 reference statements)
3
6
0
Order By: Relevance
“…This has already been suggested by Bashkin et al [1] based on the assumption that the alkali hydrides should show a similar behaviour as the alkali halides. This has already been suggested by Bashkin et al [1] based on the assumption that the alkali hydrides should show a similar behaviour as the alkali halides.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This has already been suggested by Bashkin et al [1] based on the assumption that the alkali hydrides should show a similar behaviour as the alkali halides. This has already been suggested by Bashkin et al [1] based on the assumption that the alkali hydrides should show a similar behaviour as the alkali halides.…”
Section: Discussionsupporting
confidence: 54%
“…Bashkin et al [1] have pointed out, that as in the case of most alkali halides with NaCl-type structure, the alkali hydrides may also undergo a structural phase transition to a CsCl-type structure when high pressure is applied. Bashkin et al [1] have pointed out, that as in the case of most alkali halides with NaCl-type structure, the alkali hydrides may also undergo a structural phase transition to a CsCl-type structure when high pressure is applied.…”
Section: Introductionmentioning
confidence: 99%
“…This tendency is similar to that observed for alkali-metal halides. 22,28 Data of Hochheimer and Bashkin were in relatively good agreement. Hochheimer et al, in spite of much higher range of available pressure (28 GPa) also were unable to trace the B1-B2 transition in NaH but derived the value of bulk modulus for B1 phase of this hydride.…”
supporting
confidence: 60%
“…It has been found that at high pressure the B1-type halides transform into B2-type structure. [19][20][21] Following this observation Bashkin et al 22,23 measured volume of potassium and cesium hydrides as a functions of pressure. In these experiments they used tungsten carbide piston-cylinder device so the in situ determination of structural changes was not possible.…”
Section: Alkali Metal Hydridesmentioning
confidence: 99%
See 1 more Smart Citation